KARAKTER ANATOMI DAN FISIOLOGI TANAMAN JAMBU METE (Anacardium occidentale L.) YANG DITANAM PADA TANAH PASCATAMBANG EMAS DENGAN PEMBERIAN PUPUK KANDANG SAPI - Sri Ambardini; Indrawati .; Hasmiah . (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2015)
The purpose of this study was to determine: anatomy character (density, length, and width of stomata), chlorophyll content index, and alkaloids content of plant cashew leaves (Anacardium occidentale L.) planted on gold post-mining soil Bombana with variation dose of cow manure. The experimental research use completely randomized design with four treatments, namely without cow manure (S0), and treatment of cow manure 100g 10kg-1 soil (S1), 125g 10kg-1 soil (S2), and 150g 10kg-1soil (S3)  in repeated 3 times. Anatomy of leaves Cashew plant parameters observed were the levels of density stomata, length stomata, width stomata, and the physiology were chlorophyll content index and alkaloids content. Test data using Anova and continued with LSD (density stomata), and BJND (chlorophyll content index) level of 95%. The results showed that cow manure of the treatments S3 gives the highest value of density stomata (16,98 mm2), length stomata (122, 24 µm), width stomata (109, 97 µm) and chlorophyll content index is (42,81 CCI) while on treatments alkaloids content highest S0 is (0,005 g). Cow Manure is significantly influence of stomata density  and chlorophyll content index, but no significant effect on the stomata length, stomata width and alkaloids content. Keywords : Stomata, Chlorophyll Content Index, Alkaloids Content, Cow Manure, Plant Cashew  Gold Post-Mining Soil.